2021
DOI: 10.3389/fmars.2020.597553
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Production of Astaxanthin by Co-culture of Paracoccus haeundaensis and Lactic Acid Bacteria

Abstract: This study aimed to determine the increase in astaxanthin production from Paracoccus haeundaensis by optimizing the medium conditions and co-culturing with lactic acid bacteria. In order to select a suitable strain to co-culture with P. haeundaensis, several strains were co-cultured with P. haeundaensis. Lactobacillus fermentum was selected as the optimal strain. Further to optimize the astaxanthin production in the co-culture, various medium conditions were tested and the PMF medium developed in this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…This pigment has been reported in Flavobacterium species, Paracoccus zeaxanthinifaciens, Staphylococcus aureus, and Xanthomonas oryzae (Usman et al 2018). Other pigments of bacteria colonies recorded in the previous study are astaxanthin (pinkish-red) (Choi et al 2021), canthaxanthin (dark red) (Duy et al 2021), staphyloxanthin (golden yellow) (Elmesseri et al 2022); indigoidine (blue), prodigiosin (red), pyocyanin (bluegreen) and violacein (purple) (Usman et al 2018). The previous studies on bacteria pigment recorded the capability of some bacteria to produce varieties of pigment, such as the genus Agrobacterium (Rao et al 2017), Bacillus, Chromobacterium (Usman et al 2018), Flavobacterium, Staphylococcus (Nurjahan et al 2020 and Serratia (Venil et al 2021).…”
Section: Morphological Characterization Of Endophytic Bacteriasupporting
confidence: 65%
“…This pigment has been reported in Flavobacterium species, Paracoccus zeaxanthinifaciens, Staphylococcus aureus, and Xanthomonas oryzae (Usman et al 2018). Other pigments of bacteria colonies recorded in the previous study are astaxanthin (pinkish-red) (Choi et al 2021), canthaxanthin (dark red) (Duy et al 2021), staphyloxanthin (golden yellow) (Elmesseri et al 2022); indigoidine (blue), prodigiosin (red), pyocyanin (bluegreen) and violacein (purple) (Usman et al 2018). The previous studies on bacteria pigment recorded the capability of some bacteria to produce varieties of pigment, such as the genus Agrobacterium (Rao et al 2017), Bacillus, Chromobacterium (Usman et al 2018), Flavobacterium, Staphylococcus (Nurjahan et al 2020 and Serratia (Venil et al 2021).…”
Section: Morphological Characterization Of Endophytic Bacteriasupporting
confidence: 65%
“…In a relevant reference concerning astaxanthin production, the pathway associated with this bacterium has been previously documented by other studies [ 27 ]. Therefore, we also explored the potential for producing this value-added product in the context of batch fermentation under nitrogen-limited conditions for PHA production.…”
Section: Resultsmentioning
confidence: 88%
“…Although 4 g l -1 of residual glucose remained unconsumed at the end of cultivation, optical densities reached 4.0, indicating that P. haeundaensis is an auxotroph that requires vitamins which include pyridoxine, riboflavin, pantothenic acid, and nicotinic acid. Although previous studies have reported that LB broth containing 30 g l -1 NaCl (modified LB) can provide the complete cell growth requirements for efficient astaxanthin production for this bacterium [ 27 ], such medium containing complex organic nitrogen sources, including tryptone and yeast extract, was not suitable for producing nitrogen-limiting and excess carbon conditions in this bacterium.…”
Section: Resultsmentioning
confidence: 99%
“…Several novel targets, such as probiotics which produce retinoic acid, an important metabolite for the generation of T-regs [ 144 ], the increased production of antioxidants such as astaxanthin [ 145 ], or even the quorum-sensing capacities of the microorganism [ 146 ], will be crucial parts of the probiotic screening for their application in different models and pathologies. In addition, the newest identification and characterization techniques are evolving so fast that they include organoid culture, spheroids [ 141 ], big data, and machine learning, which will soon be everyday tools for probiotics identification [ 147 ].…”
Section: Discussionmentioning
confidence: 99%